Beyond Uncertainty: Exploring Demographic Drivers of Sharia Insurance Adoption in Indonesia - Gunawan, Gugun; Juhadi, Juhadi; Mutiah, Ridla (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This research is motivated by the fact that human life is inevitably exposed to various risks, both economic risks such as business bankruptcy, fires, and losses, as well as personal risks such as accidents, illnesses, and even death. Although death is certain, the exact time of its occurrence is unknown. The purpose of this research is to determine the impact of demographic factors on the growth of Sharia insurance in Indonesia. This study employs a qualitative research method. The results show that insurance companies, as non-bank financial institutions engaged in risk coverage, are one of the pillars of the national economy. This is due to their ability to accept risk transfers from the public and their role in absorbing and accumulating public funds.